A conceptual framework for the implantation of enterprise applications in Small and Medium Enterprises (SMEs) - Reascos, Irving (2018)
This research addresses the implantation of ready-to-use enterprise applications in SMEs. The objective is to develop a description of the implantation process, identifying the actors involved and establishing the factors that affect the success of the whole process and of some of its components. The inceptive phase of the research is mainly based on a literature review. The Technology-Organization-Environment (TOE) framework was used to classify the influence factors already from the literature. The emerging process model combines contributions from several authors and it encompasses three phases, later sub-divided in fourteen stages: Pre-Implantation, Implantation and Post-Implantation. The work described in this article corresponds to a research phase that aims at understanding the implantation process and its major problems, in SMEs. The following stage will lead to the development of solutions that will address those problems. The article ends with a general view of the work to be done in future.